EP1206 Timely access to genetic counseling for women with epithelial ovarian cancer in Nova Scotia. (1st November 2019) - Warias, A; Ferguson, M; Chamberlain, E; Currie, L; Snow, N; Matheson, K; Penney, L; Kieser, K
Abstract : Introduction/Background: Prompt access to genetic counseling and testing is increasingly important for women with epithelial ovarian cancer (EOC) and their families. We evaluated the efficacy of a new collaborative model of care and preferences on timing for genetic counseling in Nova Scotia between Divisions of Medical Genetics and Gynecologic Oncology at Dalhousie University. Methodology: A retrospective cohort of all women diagnosed with EOC from 2012 to 2017 (n=386) was identified. Two cohorts were identified, pre and post implementation of a genetic counsellor attending weekly tumor board rounds. Wait-times to different nodes of the clinical pathway assessed. A questionnaire was sent to identify preference for timing of genetic counselling, and factors that may contribute to the decision to pursue genetic testing (n=103 living). Chi-square and Wilcoxon rank sum tests were used to compare demographic and clinical variables pre and post implementation of new model. Results: There were 386 women with EOC and 196 women were referred for genetic counseling with 89.8% seen. Most women chose testing after counseling, 93.1%. Following the implementation of a new care model in May 2016, there was a 48.2% (95%CI 39.4 to 56.7) increase in referrals for genetic counseling from 40% to 88%. The wait time from the referral to the first genetic counseling appointment decreased by 67.8 days, p<0.001. Seventy percent of survey respondents expressed that they wished to be referred for genetic counseling at the time of diagnosis or with initiation of chemotherapy. Women seen for genetic counseling, expressed that the most important reason for pursing genetic testing was for information for their family, 62%. Conclusion: This novel model of care for EOC in Nova Scotia was successful in increasing referral rates for genetic counseling, and genetic testing. Women favored referral to genetic services at the time of diagnosis, highlighting the importance for timely access. Disclosure: Disclosures: This project was funded by the Atlee Foundation and Astrazeneca